The Effect of Monetary Policy on Economic Growth in Lao PDR - Srithilat, Khaysy; Samatmanivong, Thipphavanh; Lienpaserth, Vaiyoth; Chanthavixay, Phiengsanith; Boundavong, Visanu; Douangty, Vonsy (International Journal of Economics and Financial Issues, 2022)
The empirical analysis of this study examines the effect of monetary policy on economic growth in Lao PDR. This study uses Vector Autoregressive Model (VAR) and quarterly data from the first quarter of 1995 to the last quarter of 2018. The results found that GDP was negatively responding to price level indicates that a shock in monetary policy or when the central bank adopts an expansionary monetary policy will result in consumer price level, and therefore leads to decline on the real output in the Lao economy. Moreover, this study also found negative effect of the real interest on GDP in Lao PDRD.